Phosphomimetic substitution at Ser-33 of the chloroquine resistance transporter PfCRT reconstitutes drug responses in Plasmodium falciparum - Sanchez, Cecilia P.; Cubel, Sonia Moliner; Nyboer, Britta; Jankowska-Döllken, Monika; Lanzer, Michael (The journal of biological chemistry, 2019)
The chloroquine resistance transporter PfCRT of the human malaria parasite Plasmodium falciparum confers resistance to the former first-line antimalarial drug chloroquine, and it modulates the responsiveness to a wide range of quinoline and quinoline-like compounds. PfCRT is post-translationally modified by phosphorylation, palmitoylation, and, possibly, ubiquitination. However, the impact of these post-translational modifications on P. falciparum biology and, in particular, the drug resistance-conferring activity of PfCRT has remained elusive. Here, we confirm phosphorylation at Ser-33 and Ser-411 of PfCRT of the chloroquine-resistant P. falciparum strain Dd2 and show that kinase inhibitors can sensitize drug responsiveness. Using CRISPR/Cas9 genome editing to generate genetically engineered PfCRT variants in the parasite, we further show that substituting Ser-33 with alanine reduced chloroquine and quinine resistance by ∼50% compared with the parental P. falciparum strain Dd2, whereas the phosphomimetic amino acid aspartic acid could fully and glutamic acid could partially reconstitute the level of chloroquine/quinine resistance. Transport studies conducted in the parasite and in PfCRT-expressing Xenopus laevis oocytes linked phosphomimetic substitution at Ser-33 to increased transport velocity. Our data are consistent with phosphorylation of Ser-33 relieving an autoinhibitory intramolecular interaction within PfCRT, leading to a stimulated drug transport activity. Our findings shed additional light on the function of PfCRT and suggest that chloroquine could be reevaluated as an antimalarial drug by targeting the kinase in P. falciparum that phosphorylates Ser-33 of PfCRT.
Gesehen am 11.10.2019